2019
DOI: 10.1016/j.celrep.2019.08.042
|View full text |Cite
|
Sign up to set email alerts
|

The Sympathetic Nervous System Mitigates CNS Autoimmunity via β2-Adrenergic Receptor Signaling in Immune Cells

Abstract: Highlights d Sympathetic nervous system (SNS) limits CNS autoimmune inflammation d Adrb2 signaling in immune cells mediates the SNS effects on EAE development d Adrb2-mediated SNS suppressive effects involve ICERdriven inhibition of CD4 + T cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…On one side, activation of β2-adrenergic receptors activates the homing of CD8 + effector memory T-cells and an upregulation of CCL19 and CCL21 in hypertension. On the other side, activation of β2-adrenergic receptors in experimental autoimmune disease or in vitro reduces the T-cell response to sympathetic norepinephrine and decreases the release of INF-γ and TNF-α from CD8 + T-cells (Estrada et al, 2016;Araujo et al, 2019). Although α2-adrenoceptors are expressed on T-cells, their role in T-cell function in general and particularly in hypertension is not well understood.…”
Section: Role Of Renal Sympathetic Neurotransmission and α2-adrenocepmentioning
confidence: 99%
“…On one side, activation of β2-adrenergic receptors activates the homing of CD8 + effector memory T-cells and an upregulation of CCL19 and CCL21 in hypertension. On the other side, activation of β2-adrenergic receptors in experimental autoimmune disease or in vitro reduces the T-cell response to sympathetic norepinephrine and decreases the release of INF-γ and TNF-α from CD8 + T-cells (Estrada et al, 2016;Araujo et al, 2019). Although α2-adrenoceptors are expressed on T-cells, their role in T-cell function in general and particularly in hypertension is not well understood.…”
Section: Role Of Renal Sympathetic Neurotransmission and α2-adrenocepmentioning
confidence: 99%
“…This discrepancy could be related to recent findings indicating that isoproterenol represents a novel type of α 1A -adrenoceptor partial agonist (133), and differences in propranolol dose, particularly as in the rat there are strain differences in its metabolism. Furthermore, it has recently been reported that increased systemic noradrenaline levels due to sympathoneural system hyperactivity (134) in mice constitutively lacking α 2a/c -adrenoceptor (constituting an important negative-feedback mechanism required for the presynaptic control of neurotransmitter release from sympathetic fibers) is associated with diminished pathogenic T-cell responses and CNS inflammation in EAE (135). These findings might be explained by data suggesting that prolonged sympathoneural activation (as it is in late phases of inflammatory autoimmune diseases) leads to anti-inflammatory sympathoneural action (31).…”
Section: Animal Datamentioning
confidence: 99%
“…It is well known that primary lymphoid tissue (thymus, bone marrow) as well as the spleen, lymph nodes and mucosa-associated lymphoid tissue are innervated by sympathetic nerves suggesting that NE, the major neurotransmitter released by sympathetic nerves, is involved in modulating immune responses [104][105][106]. Indeed, it has been shown that NE-induced β2 adrenergic receptor (β2-AR) signaling in T and B cells, myeloid cells and dendritic cells (DCs) modulates antigen-processing and presentation as well as T cell activation, differentiation and recirculation [104,[106][107][108][109][110][111][112][113]. A recent study by Araujo et al Fig.…”
Section: Housing Temperaturementioning
confidence: 99%
“…Reproduced from [23] with permission. References for the different studies in this figure appear in reference [23] demonstrated that the SNS limits the development of MOG 35-53 /CFA-induced experimental autoimmune encephalomyelitis (EAE) in mice via β2-AR signaling in CD4 + T cells that constrains the generation of encephalogenic effector cells [107]. In contrast, when β2-ARdeficient (β2-AR −/− ) mice were immunized with MOG 35-53 /CFA, they developed more severe disease when compared with wild type mice.…”
Section: Housing Temperaturementioning
confidence: 99%